The Incidence of Postpartum Hemorrhage in Pregnant Women with Placenta Previa: A Systematic Review and Meta-Analysis. - Dazhi Fan; Qing Xia; Li Liu; Shuzhen Wu; Guo Tian; Wen Wang; Song Wu; Xiaoling Guo; Zhengping Liu (PLoS ONE, 2017)
Background The global burden of postpartum hemorrhage (PPH) in women with placenta previa is a major public health concern. Although there are different reports on the incidence of PPH in different countries, to date, no research has reviewed them. Objective The aim of this study was to calculate the average point incidence of PPH in women with placenta previa. Methods A systematic review and meta-analysis of observational studies estimating PPH in women with placenta previa was conducted through literature searches in four databases in Jul 2016. This study was totally conducted according to the MOOSE guidelines and in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses standard. Results From 1148 obtained studies, 11 included in the meta-analysis, which involved 5146 unique pregnant women with placenta previa. The overall pooled incidence of PPH was 22.3% (95% CI 15.8-28.7%). In the subgroup, the prevalence was 27.4% in placenta previas, and was 14.5% in low-lying placenta previa; the highest prevalence was estimated in Northern America (26.3%, 95%CI 11.0-41.6%), followed by the Asia (20.7%, 95%CI 12.8-28.6%), Australia (19.2%, 95% CI 17.2-21.1%) and Europe (17.8%, 95% CI, 11.5%-24.0%). Conclusions The summary estimate of the incidence of PPH among women with placenta previa was considerable in this systematic review. The results will be crucial in prevention, treatment, and identification of PPH among pregnant women with placenta previa and will be contributed to the planning and implantation of relevant public health strategies.